Influences of Process Temperature on a Phase of Ga2O3 Thin Films Grown by Atomic Layer Deposition on Sapphire - Lee, Seung Hyun; Lee, Kang Min; Lee, Sang Woon (Bulletin of the Korean Chemical Society, 2020)
Influences of process temperature on the phase of Ga2O3 thin films grown by atomic layer deposition (ALD) on a sapphire substrate is investigated. Ga2O3 thin films grown by ALD at a process temperature of 200°C showed an amorphous phase; however, crystalline α-Ga2O3 film was deposited at the deposition temperatures from 225 to 250°C. Above a process temperature of 300°C, α and β phases coexist in the grown Ga2O3 thin film. Interestingly, β-Ga2O3 thin film was deposited on the sapphire by an increase of working pressure during Ga2O3 ALD process at the process temperature of 300°C. The bandgap of β-Ga2O3 thin film was as high as ~5.2 eV. A metal–semiconductor–metal type photodetector using the β-Ga2O3 thin film exhibited a fast response speed with a short rise time of 1.3 μs for the detection of deep ultraviolet wavelengths.
Keywords: Amorphous phase; Deep ultraviolet; Deposition temperatures; Fast response; Metal types; Process temperature; Sapphire substrates; Working pressures; Atomic layer deposition; Ga2O3; Phase; Process temperature; Thin film